High strain rate characterization of thermoplastic fiber-reinforced composites under compressive loading - Ramírez Montes, Carolina; Reis, Vitor; Opelt, Carlos; Santiago, Rafael; Almeraya Calderón, Facundo; Donadon, Mauricio V; Gaona Tiburcio, Citlalli; Croche, René; Baltazar Zamora, Miguel Ángel (Intechopen, 2019)
Experimental study on the mechanical behavior of polyphenylene sulfide (PPS)-based composite laminates reinforced with carbon and glass fibers subjected to different strain rates under compression load is reported. Quasi-static tests have been carried out using an electromechanical universal testing machine at three different strain rates, while dynamic tests were done using a split-Hopkinson pressure bar (SHPB) apparatus at two pressure setups in the gas chamber. High-speed imaging system was used to monitor failure process during dynamic test, and these images were used to measure strain by digital image correlation (DIC) in order to compare the DIC-based measurements performed with the SPHPB strain gauges and quasi-static results. Fractography analysis was also performed to identify the main failure mechanisms induced at different strain rates.